The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1259/bjr.20150022
|View full text |Cite
|
Sign up to set email alerts
|

Acute anal toxicity after whole pelvic radiotherapy in patients with asymptomatic haemorrhoids: identification of dosimetric and patient factors

Abstract: Objective: Patients with asymptomatic haemorrhoids are known to be less tolerant of radiation doses lower than known tolerance doses. In the present study, the authors sought to identify the risk factors of acute haemorrhoid aggravation after whole pelvic radiotherapy (WPRT). Methods: The records of 33 patients with cervical, rectal or prostate cancer with asymptomatic haemorrhoids, which were confirmed by colonoscopy before the start of radiotherapy (RT), were reviewed. Acute anal symptoms, such as anal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…Similar results were also observed in validation cohort, in which AAT developed in 44.2% of the patients with hemorrhoids, but only in 17.0% of the patients without hemorrhoids. Our results also confirm the high frequency of AAT (42.4–50%) after whole pelvic irradiation of 45–50.4 Gy for pelvic malignant disease reported previously in Korean patients with asymptomatic hemorrhoids [11, 12]. Interestingly, few studies from America and Europe have addressed this topic, mainly because both hemorrhoids and AAT are less common in patients in these regions, and the symptoms are usually mild and resolve spontaneously [5, 17, 18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were also observed in validation cohort, in which AAT developed in 44.2% of the patients with hemorrhoids, but only in 17.0% of the patients without hemorrhoids. Our results also confirm the high frequency of AAT (42.4–50%) after whole pelvic irradiation of 45–50.4 Gy for pelvic malignant disease reported previously in Korean patients with asymptomatic hemorrhoids [11, 12]. Interestingly, few studies from America and Europe have addressed this topic, mainly because both hemorrhoids and AAT are less common in patients in these regions, and the symptoms are usually mild and resolve spontaneously [5, 17, 18].…”
Section: Discussionsupporting
confidence: 91%
“…The median induction dose for AAT is about 37.5 Gy (38.3 Gy calculated as EQD2) in our study, which is similar to the results of the two studies from Korea (34.1–36.9 Gy) [11, 12]. However, none of the DVH parameters were significant predictors of AAT in their studies, and only V10 or V30 and V40 showed marginal correlations with AAT [11, 12]. Indeed, it is difficult to draw reliable conclusions from two studies with such small sample sizes of 31 and 33 patients, and DVH predictors of AAT should be re-evaluated in larger patient cohorts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study was focused on the acute anal complication in patients with haemorrhoids, and the published study 11 about acute anal toxicity is rare. A previous study 29 demonstrated that 34.1 Gy is the induction dose of acute anal symptoms in patients with haemorrhoids, and we conservatively chose the dose objective of the anal canal. To apply IM-WPRT plan in the clinical field, the accurate target delineation and the proper dose constraint of the anal canal is a requisite.…”
Section: Discussionmentioning
confidence: 99%